Happiness is within oneself / Nor Haniza Hasan, Dr. Tuan Sarifah Aini Syed Ahmad - Hasan, Nor Haniza; Syed Ahmad, Tuan Sarifah Aini (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
In today’s society, people usually measure their happiness by external markers such as social validation, career achievements and wealth. The markers are often not so stable that can cause dissatisfaction or stress when the markers are not aligned with their personal expectations. The concept of “happiness is within oneself” is not new as many thinkers have explored it. This concept is powerful as it reminds us that true happiness comes from the internal states such as personal development, self-acceptance, self-awareness and the application of practical strategies in accomplishing things. Personal development is significant for inner fulfilment. It comprises of relationships, work, or personal growth, setting personal objectives that can lead to a deep sense of achievement. It emphasizes not just achieving external successes but also developing ourselves as individuals.